2010
DOI: 10.1371/journal.pone.0012713
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling-Based Evaluation of hTLR10 and Identification of Potential Ligands in Toll-Like Receptor Signaling

Abstract: Toll-like receptors (TLRs) are pattern recognition receptors that recognize pathogens based on distinct molecular signatures. The human (h)TLR1, 2, 6 and 10 belong to the hTLR1 subfamilies, which are localized in the extracellular regions and activated in response to diverse ligand molecules. Due to the unavailability of the hTLR10 crystal structure, the understanding of its homo and heterodimerization with hTLR2 and hTLR1 and the ligand responsible for its activation is limited. To improve our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 41 publications
0
66
0
Order By: Relevance
“…Along this line, we addressed whether the 2 CD27 ϩ subsets have different effector profiles in response to various TLR agonists, including PamCys-(Pam)SK4, a proposed TLR10-specific ligand based on modeling studies. 33 Unfortunately, no response either in terms of cytokine/ chemokine secretion or cellular proliferation was observed for this agonist, thus precluding to get insight as to whether TLR10 may have a unique function for IgM ϩ IgD ϩ CD27 ϩ cells. We found that TLR2/6, TLR7, and TLR9 triggering activated all splenic subsets to produce cytokines, chemokines, and hematopoietic growth factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along this line, we addressed whether the 2 CD27 ϩ subsets have different effector profiles in response to various TLR agonists, including PamCys-(Pam)SK4, a proposed TLR10-specific ligand based on modeling studies. 33 Unfortunately, no response either in terms of cytokine/ chemokine secretion or cellular proliferation was observed for this agonist, thus precluding to get insight as to whether TLR10 may have a unique function for IgM ϩ IgD ϩ CD27 ϩ cells. We found that TLR2/6, TLR7, and TLR9 triggering activated all splenic subsets to produce cytokines, chemokines, and hematopoietic growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Sorted B cells were incubated in 96-well flat-bottom plates (BD Biosciences) at a concentration of 2 ϫ 10 5 cells/200L in RPMI1640/Glutamax/ PenStrep (Gibco-Invitrogen) and 10% FCS (FetalClone I; HyClone) and were stimulated with different TLR agonists, used at the following final concentrations: CpG ODN 2006 (TLR9 agonist, Sigma-Aldrich) at 6 g/ mL; flagellin (TLR5 agonist) at 0.5 g/mL; resiquimod or R848 (TLR7 and 8 agonist), Pam2CSK4 (TLR2/6 agonist), and Pam3CSK4 (TLR1/2 agonist; all from Invivogen) at 1 g/mL; PamCys(Pam)-SK4 (a putative TLR10 agonist, 33 EMC Microcollections) at 1 g/mL; and poly-IC (polyinosine-polycytidic acid, a TLR3 agonist, GE Healthcare) at 25 ng/L. The quantitative determination of secreted cytokines/chemokines was performed on 96-well supernatants collected after 4 days in culture via the use of multiplex cytokine assays (Human Cytokine 25-plex panel from Invitrogen or Bio-Plex Pro Human Cytokine 27-Plex Panel from Bio-Rad) read on a Bio-Plex 200 system (Bio-Rad).…”
Section: B-cell Culture With Tlr Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is low evidence about the ligands binding TLR10. A study carried out by Govindaraj et al [62] showed that PamCysPamSK4, a di-acylated peptide, might activate the human TLR10/1 hetero and TLR10 homodimer, while Pam3CSK4 might be recognized by the TLR10/2 heterodimer.…”
Section: Targeting Dendritic Cellsmentioning
confidence: 99%
“…Homology models of TLR10 complexes were built and refined through molecular dynamics (MD) simulations to predict the protein–ligand complexes hTLR2‐hTLR10‐Pam 3 CSK 4 , hTLR1‐hTLR10‐PamCysPamSK 4 and hTLR10‐hTLR10‐PamCysPamSK 4 28 . X‐ray crystallography studies of dimeric complexes of TLR2 in combination with TLR1, which recognizes Pam 3 CSK 4 , and another combination of TLR2 with TLR6, which recognizes Pam 2 CSK 4 , have dissected ECDs of the TLR2 subfamily 17.…”
Section: Introductionmentioning
confidence: 99%